Unraveling the “golden ratio”: a pilot study investigating acute-to-chronic workload ratio in breast cancer patients undergoing active treatment - Skouras, Apostolos Z.; Antonakis-Karamintzas, Dimitrios; Tsolakis, Charilaos; Koulouvaris, Panagiotis (Frontiers in Physiology, 2024)
Training load monitoring is a common practice in sports medicine for supporting athletes' health and performance. Despite progress in exercise oncology research for breast cancer patients, training load monitoring is underutilized. This study retrospectively investigated the relationship between maintained training load within a defined range and physical and health outcomes of ten breast cancer patients during active anticancer treatment who underwent a 12-week exercise program. Intervention consisted of endurance and resistance training, three times a week, with each session lasting 30-45 minutes. Assessments were conducted at baseline, 6 and 12 weeks after enrollment, evaluating physical function (6-minute walk test -6MWT, and sit-to-stand), muscle strength, body composition, sleep quality (Pittsburgh Sleep Quality Index -PSQI), quality of life (EORTC-QLQ-C30), heart rate variability (HRV), and physical activity levels (International Physical Activity Questionnaire -IPAQ). The Physiological Cost Index/Energy Expenditure Index (PCI/EEI) was estimated using the 6MWT and HR. Training load monitoring was performed by session rating of perceived exertion (sRPE, relative intensity multiplying with session duration). Acute-to-Chronic Workload Ratio (ACWR) (7:28, rolling average) was calculated accordingly. Analyses were performed within-subjects across time points and between-subjects, comparing those who maintained from weeks 6 to 12 an ACWR of 0.8-1.3 with those who did not. Adherence rates were similar between groups. Physical function improved in the total sample with large effect sizes (Δ6MWT = 56.5m [95%CI: 6-100m], effect size [w] = 0.52, p = 0.006; ΔSit-to-Stand = 1.5 [95%CI: 1-5], effect size [w] = 0.681, p < 0.001), demonstrating greater changes in patients with higher ACWR. Sleep quality improvements were higher in the appropriate ACWR group (p = 0.016). A positive correlation was demonstrated between global health status and 6MWT change from baseline to 12 weeks (ρ=0.689, p=0.04). Despite a small sample size, patients maintaining sufficient relative training load presented greater physical fitness and sleep quality improvements. Thus, training load monitoring may enhance exercise program benefits in breast cancer patients under active treatment.